Tolerance of dark septate endophytic fungi (DSE) to agrochemicals in vitro - Spagnoletti, Federico Nicolás (2019)
Dark septate endophytes (DSE) are a heterogeneous group of fungi, mostly belonging to the Phylum Ascomycota, that are involved in a mutualistic symbiosis with plant roots. The aim of this study is to evaluate the behavior of two strains of DSE isolated from wheat roots of two cropping areas in the province of Buenos Aires, Argentina, against some agrochemicals. Of all the isolates obtained, two strains were identified as Alternaria alternata and Cochliobolus sp. These DSE were found to be tolerant to glyphosate, carbendazim and cypermethrin when evaluated at the recommended agronomic dose (AD), 2 AD and, in some cases, 10 AD. This work contributes to the study of the biology of this group of fungi and their tolerance in the presence of xenobiotics widely used in agriculture.